2013
DOI: 10.5204/ijcjsd.v2i2.115
|View full text |Cite
|
Sign up to set email alerts
|

Toxic State–Corporate Crimes, Neo-liberalism and Green Criminology: The Hazards and Legacies of the Oil, Chemical and Mineral Industries

Abstract: This paper uses examples from the history and practices of multi-national and large companies in the oil, chemical and asbestos industries to examine their legal and illegal despoiling and destruction of the environment and impact on human and non-human life. The discussion draws on the literature on green criminology and state-corporate crime and considers measures and arrangements that might mitigate or prevent such damaging acts. This paper is part of ongoing work on green criminology and crimes of the econ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 58 publications
(26 citation statements)
references
References 35 publications
0
24
0
2
Order By: Relevance
“…Criminological theories on situational crime prevention have stressed the importance of 'target hardening' as a key strategy in the prevention of cybercrime [16]. Situational crime prevention theories place the responsibility for prevention of cybercrime with corporations as potential victims, an approach that is also taken in corporate crime literature about the prevention of environmental harm and industrial accidents [17][18][19][20][21]. In line with these approaches, this paper investigates what efforts corporate actors currently take to protect themselves, and what role public authorities should play in governing corporate cybersecurity.…”
Section: Aim Of This Studymentioning
confidence: 99%
See 1 more Smart Citation
“…Criminological theories on situational crime prevention have stressed the importance of 'target hardening' as a key strategy in the prevention of cybercrime [16]. Situational crime prevention theories place the responsibility for prevention of cybercrime with corporations as potential victims, an approach that is also taken in corporate crime literature about the prevention of environmental harm and industrial accidents [17][18][19][20][21]. In line with these approaches, this paper investigates what efforts corporate actors currently take to protect themselves, and what role public authorities should play in governing corporate cybersecurity.…”
Section: Aim Of This Studymentioning
confidence: 99%
“…It describes the collaborate governance structure of cybersecurity in chemical industries, the efforts of chemical firms in the port of Rotterdam to prevent industrial hazards related to cybercrime, and the role of public authorities in ensuring corporate cybersecurity. Criminological scholarship on industrial hazards, corporate environmental harm and corporate negligence has frequently demonstrated how corporations fail to invest in adequate measures to protect their personnel and environment from accidents [18,20,29,30]. This paper adds to this scholarship by studying how firms prevent industrial hazards and environmental harms caused by cybercrime.…”
Section: Aim Of This Studymentioning
confidence: 99%
“…Pour ceux qui étudient ce type de dégradation environnementale et son lien avec de considérables dommages écologiques et sociaux, le concept de criminalité environnementale des États et des entreprises semble fort approprié (Ruggiero et South, 2013 ;Smandych et Kueneman, 2010). Dans le contexte mondial des changements climatiques, la taille et l'impact de ce genre d'exploitation rejoignent égale-ment parfaitement le concept d'écocide.…”
Section: Les Changements Climatiquesunclassified
“…What is being contested here is not so much the nature of differing views about global warming or climate change, or environmental issues in general, but the merit or otherwise of markets operating according to principles of regulation versus neo-liberalism (see also Ruggiero and South 2013). As Lewandowsky (2011) suggests, '[i]f emissions must be cut, then markets must be regulated or at least "nudged" towards alternative sources of energy -and any possibility of regulation is considered a threat to the very essence' of the worldview of those 'for whom the free market is sacrosanct'.…”
Section: Criminology and Climate Changementioning
confidence: 99%